APPLICATION OF PROJECT-BASED LEARNING IN EFL CLASS - Fayziyev Abbos; Begizova Madina Karimovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: The article is devoted to the consideration of the use of the project-based learning in the process of teaching English in senior secondary schools. In it, based on the study of the relevant literature, a number of its advantages are identified and some suggestions are proposed around which a lesson can be built using the mentioned method. In the article, also, based on his experience of working with senior school students, the author offers his own version of conducting a lesson on creating a short film based on the project method, highlighting several mandatory stages preceding its creation.